2022
DOI: 10.3389/fgene.2022.928754
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the KCNQ1OT1/ miR-378a-3p/ RBMS1 Axis as a Novel Prognostic Biomarker Associated With Immune Cell Infiltration in Gastric Cancer

Abstract: Background: Gastric cancer (GC) is the second leading cause of cancer-related mortality and the fifth most common cancer worldwide. However, the underlying mechanisms of competitive endogenous RNAs (ceRNAs) in GC are unclear. This study aimed to construct a ceRNA regulation network in correlation with prognosis and explore a prognostic model associated with GC.Methods: In this study, 1,040 cases of GC were obtained from TCGA and GEO datasets. To identify potential prognostic signature associated with GC, Cox r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Our findings demonstrated that GA treatment at any dose level led to significant reductions in the score, frequency, and duration of epileptic seizures in TLE young rats, and exhibited the best efficacy at the dosage of 60 mg/kg. A prior study suggested that GA is absorbed into the blood, which then crosses the blood–brain barrier (BBB) to reach the brain and exert its protective effects, which is a possible explanation for our findings 23 . Additionally, evidence has come to light indicating the presence of ferroptosis in the hippocampus after TLE 6 .…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Our findings demonstrated that GA treatment at any dose level led to significant reductions in the score, frequency, and duration of epileptic seizures in TLE young rats, and exhibited the best efficacy at the dosage of 60 mg/kg. A prior study suggested that GA is absorbed into the blood, which then crosses the blood–brain barrier (BBB) to reach the brain and exert its protective effects, which is a possible explanation for our findings 23 . Additionally, evidence has come to light indicating the presence of ferroptosis in the hippocampus after TLE 6 .…”
Section: Discussionsupporting
confidence: 52%
“…A prior study suggested that GA is absorbed into the blood, which then crosses the bloodbrain barrier (BBB) to reach the brain and exert its protective effects, which is a possible explanation for our findings. 23 Additionally, evidence has come to light indicating the presence of ferroptosis in the hippocampus after TLE. 6 Moreover, GA can elicit strong neuroprotective effects in rodent models of vascular dementia via inhibition of oxidative stress and diminishing the release of cytochrome-c. 30 Wang Y et al highlighted that GA can attenuate the degree of ferroptosis in acute liver failure through the inhibition of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ting Yue et al. found that the KCNQ1OT1/miR-378a-3p/RBMS1 axis may be a potential prognostic biomarker and provide insights into the molecular mechanisms of GC pathogenesis ( 28 ). LncRNA MAGI2-AS3 is an ideal biomarker and could be a potential therapeutic target for GC ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput sequencing analysis has revealed many deregulated lncRNAs in human cancers, and abnormal expression of lncRNAs is related to tumor recurrence and metastasis (10, 26, 27). For example, Ting Yue et al found that the KCNQ1OT1/miR-378a-3p/ RBMS1 axis may be a potential prognostic biomarker and provide insights into the molecular mechanisms of GC pathogenesis (28). LncRNA MAGI2-AS3 is an ideal biomarker and could be a potential therapeutic target for GC (29).…”
Section: Expression and Functional Analysis Of Six Angiogenesis-relat...mentioning
confidence: 99%